Pengaruh Brand Awareness, Brand Images Dan Perceived Quality Terhadap Loyalitas Pelanggan (Studi Pada Mahasiswi Kota Malang yang melakukan Pembelian di Clodia Outfit) - Sulyantri, Sulfy; Mustapita, Arini Fitria; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the simultaneous or partial influence of Brand Awareness, Brand Images, and Perceived Quality on Customer Loyalty at Clodia Outfit. This type of research uses a quantitative approach method. The population in this study were female students from Malang City. Determining the sample in this research was carried out using a purposive sampling technique, namely a technique for selecting samples based on the special characteristics of the sample. Researchers will later take samples from Malang City students who made purchases at Clodia Outfit more than once. Simultaneously and partially, Brand Awareness, Brand Images, and Perceived Quality have a significant effect on Customer Loyalty among female students in Malang City. Keywords: Brand Awareness, Brand Images, Perceived Quality dan Customer Loyalty